Pengaruh Kepuasan Konsumen terhadap Brand Produk Minuman Boba Xing Fu Tang - Aulia Khairunisa; Puspita Chairun Nisa (Jurnal Ecodemica : Jurnal Ekonomi Manajemen dan Bisnis, 2022)
This research was conducted to see the influence and relationship between price promotion, brand image, product quality, perceived value and consumer satisfaction. And to determine the effect of customer satisfaction on repurchase intentions, brand loyalty, and electronic word of mouth. The results of this study are expected to add information at the theoretical/scientific level of Marketing Management as well as positive managerial implications on business management. The study used a survey method as data collection using online instrumentation with a target population of the millennial generation between the ages of 18 to 40 years in Bekasi. Data collection was carried out during the COVID-19 pandemic. The sample used in this study amounted to 130 respondents, and processing and data analysis using Smartpls and SPSS software. (1) price promotion, and product quality do not affect consumer satisfaction, (2) brand image, and perceived value have an effect on consumer satisfaction, (3) customer satisfaction on repurchase intentions, brand loyalty, and electronic word of mouth have a positive and significant effect .Keywords: price promotion, brand image, product quality, customer satisfaction